Ciência, disciplina e manual: É. Benveniste e a lingüística da enunciação - Giacomelli, Karina (2007)
This paper presents an analysis of introductory manuals to linguistics published in Brazil in the last two decades, with the aim of identifying references to Benveniste. The manualization of linguistic knowledge on enunciation is considered a larger process of disciplinarization, in which two types of contextualization are confronted: that of the constituition of scientific knowledge and that of the school world. In this respect, the notion of discipline is explored as a field that must select its domains in regard to others : those that have preceded it and those that are adjacent to it, while still projecting a path of development for itself. It thus comprises a horizon of retrospection, a horizon of projection and a domain of contemporaneity and these three dimensions provide the conditions for knowledge to be conveyed within the school world. This characterizes the process of didatic transposition, in which scientific knowledge undergoes transformations that allow it to be taught. One of the formats in which it materializes into is the manual, a priviledged vehicle for the construction of disciplinary discourse. What the analysis of instructional books reveals is that the lack of an institutionalized discipline linguistics of enunciation is reflected in the mannual, once the short space granted to Benveniste s theory does not allow one to know enough the author who made it possible a new form of viewing and studying language: language transformed into discourse through enunciation.